ANALISIS LAMA SEKOLAH DI PROVINSI JAWA TENGAH PROVINSI JAWA TENGAH - Safitri, Mellyana; Firdaus, Wahyu Tri Nur Ahmad; Nuryadi, Didi (International Journal of Multidisciplinary Research and Literature, 2024)
This study explores the expected years of schooling through the formal education level pursued by the people of Central Java province from 2018 to 2021. This study also suggests that other factors, such as income and social conditions, also affect Central Java Province's schooling length. Human resources are the core of life, so they must be considered to create superior resource capabilities. The method used in this research is quantitative with panel data regression analysis. The results showed that the average years of schooling variable had a positive and insignificant effect on the expected years of schooling, and the district minimum wage variable had a positive and significant effect on the expected years of schooling. From these results, it is concluded that the effect of the independent variable of average years of schooling and city minimum wage on the dependent variable of long school expectation with a study of 6 cities in Central Java through the results of the r-square calculation of 49.87%. The remaining 50.13% is influenced by independent variables outside of the average length of schooling and the city's minimum wage